Creativity in education - Abdul Rahman, Shukran (USM Press, 2019)
The books provide a platform for writers from all over the world to discuss and debate critical issues that underlie higher education locally and globally. Subjects such as governance, reform, rankings, sustainability, futures, and many more are dissected and analysed. Because the results would eventually and inevitably affect higher education policies in the region, specifically in Malaysia, the series serves as a valuable resource for researchers, policymakers, administrators, and practitioners. The matters discussed would be a reflection and a sounding board for all parties involved in higher education.